A normal paediatric amylase range. Issue 3 (March 1980) - Aggett, P J; Taylor, F
Abstract : A normal paediatric range of plasma alpha-amylase activity was determined using the Phadebas blue starch method. The range for children over one year was 98–405 IU/l. Plasma amylase activity increased throughout infancy. Mature levels of activity were observed in some children by age 2 months and in most of them by 9 months.